2022
DOI: 10.1021/acsestwater.1c00479
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Transformations of Perfluoroalkyl Acid (PFAA) Precursors and PFAAs in Landfill Leachates

Abstract: Landfill leachates possess a countless number of chemical classes of potential environmental and human concern, including per- and polyfluoroalkyl substances (PFAS). While detection and biodegradation studies of PFAS in leachates have been conducted previously, the degradation of precursors of perfluoroalkyl acids (PFAAs) in landfill leachates with oxidative technologies has not been addressed. Thus, information regarding the oxidative transformations of PFAA precursors typically present in leachates is lackin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…Since SF 5 -PFSAs are perfluorinated and were not transformed in the dTOP assay (see the following section), the unsaturated SF 5 -PFSAs are expected to be side products rather than transformation products. In general, PFAS with SF 5 groups were detected in AFFFs and commercial products, ,, in biosolids and organic waste, as well as in landfill leachates, and waste water related to electronics fabrication, however, to our knowledge never as the primary PFAS contamination. Barzen-Hanson et al (2017) found SF 5 -PFAS in 3M patents from 1992 and detected them in technical products but not in groundwater.…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Since SF 5 -PFSAs are perfluorinated and were not transformed in the dTOP assay (see the following section), the unsaturated SF 5 -PFSAs are expected to be side products rather than transformation products. In general, PFAS with SF 5 groups were detected in AFFFs and commercial products, ,, in biosolids and organic waste, as well as in landfill leachates, and waste water related to electronics fabrication, however, to our knowledge never as the primary PFAS contamination. Barzen-Hanson et al (2017) found SF 5 -PFAS in 3M patents from 1992 and detected them in technical products but not in groundwater.…”
Section: Resultsmentioning
confidence: 74%
“…Due to the fact that SF 5 -PFSAs seem to be the major PFAS contaminants in the BS-NRW soil, it is reasonable to assume that the contamination of the BS-NRW soil goes back to specific sources and unknown products. Previously reported SF 5 -PFAS in environmental samples were minor contaminants compared to other detected PFAS. , …”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…The heterogeneous CPAO process includes two steps: () the diffusion of persulfate to the cathode surface from bulk solution (i.e., mass-transfer) , and () the activation of persulfate to produce SO 4 •– (i.e., charge-transfer) . Current studies on the CPAO process, using conventional electrochemical reactors with parallel plates operated in the batch/flow-by mode, commonly featured a poor mass-transfer performance, resulting in the low efficiency of persulfate activation and long hydraulic retention times (e.g., several hours) for water treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Ammonia-nitrogen is a ubiquitous pollutant in different kinds of wastewater and discharge of this critical nutrient into waterbody that will lead to water body eutrophication and exhibit potential risks to aquatic life. Conventional microbial processes based on ammonia removal techniques are suitable for centralized sewage water treatment, whereas the physicochemical approaches, such as membrane separation, ion exchange, air stripping, breakpoint chlorination, and advanced oxidation techniques, are suitable for small scale or in situ water or wastewater treatment. Among the different types of physicochemical approaches, electrochemical (EC) oxidation of ammonia, particularly indirect EC oxidation relying on in situ producing reactive chlorine species, exhibits promising application prospect for the treatment of different types of wastewater containing ammonia and chloride ion, which attracts significant attention in academic research and industrial application. …”
Section: Introductionmentioning
confidence: 99%